2012
DOI: 10.1038/nbt.2198
|View full text |Cite|
|
Sign up to set email alerts
|

Performance comparison of benchtop high-throughput sequencing platforms

Abstract: Three bench-top high-throughput sequencing instruments are now available. The 454 GS Junior (Roche), MiSeq (Illumina) and Ion Torrent PGM (Life Technologies) are laser-printer sized and offer modest set-up and running costs. Each instrument can generate a draft bacterial genome sequence in days, making them attractive for use in the identification and characterization of pathogens in the clinical setting. We compared the performance of these instruments by sequencing isolates of Escherichia coli O104:H4 from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
1,001
3
10

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,212 publications
(1,058 citation statements)
references
References 24 publications
34
1,001
3
10
Order By: Relevance
“…In the near future, with such new platforms as Miseq or Ion Torrent PGM, the testing cycle could be shortened to just a few days. 25 Furthermore, the cost of analyzing an individual sample is much lower than that using MLPA plus Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In the near future, with such new platforms as Miseq or Ion Torrent PGM, the testing cycle could be shortened to just a few days. 25 Furthermore, the cost of analyzing an individual sample is much lower than that using MLPA plus Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…As the throughput and read length of SGS continue to improve, soon it will be feasible to sequence the entire MHC in a few reads in just a few hours, eliminating time delay as a barrier to the use of HLA matching data to inform the treatment of solid organ transplant (SOT) recipients (eg, in pre-transplant immunosuppressive dosing). 18 …”
Section: Box 1 New Genomics Technology In Hctmentioning
confidence: 99%
“…They identified that D À/R þ status for one particular GEMA UGT2B17 increased the risk of Grade 2 þ GVHD, a finding that was later replicated in two independent cohorts, together totaling over 1300 patients (combined OR of 2.5). 18 In addition, McCarroll et al showed that UGT2B17 þ HCT recipients, who received hematopoeitic cells from UGT2B17 À/ À donors were seropositive for anti-UGT2B17 antibodies. Moreover, they were able to isolate MHC-bound UGT2B17-derived peptides from the sera of these UGT2B17 mismatched.…”
Section: Application Of Pharmacogenomics (Pgx) To Hctmentioning
confidence: 99%
See 2 more Smart Citations